Indoleamine-2,3-Dioxygenase Gene Expression in Cryopreserved Fetal Nerve Cells - Porozhan, Eugeniya A.; Dimitrov, Aleksey Yu.; Babenko, Nataliya N.; Dubrava, Tatyana G.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â  Probl Cryobiol Cryomed 2014; 24(2):160.